Adapting inclusive design concepts in developing assistive mobility design system for PWDs specific community in Malaysia using Design Develop Research (DDR) - Ariff, Ahnad Fairuz; R, Rahman.; Z S, Zainol Fithri.; Qiu, Liping (Human Resources Management Academic Research Society (HRMARS), 2024)
Many current design development processes include design concepts for users, but there is still room for improvement and time for design concepts to be executed, thoroughly researched, and altered to be significant throughout the product development stages. The role of Inclusive Design (IDA) is recognized as one of the significant alternatives to produced design such as an Assistive Mobility Design System (AMDS) to stimulate movement of persons with disabilities (PWDs), as well as to simplify their journey throughout the environment to cater everyday demands. This study aims to apply Design Development Research (DDR) approaches in order to further comprehend the consumers and specific items studied and observed. The data was gathered by 10 different wheelchair users and 5 experts, include designers, engineers, and society officers. This assignment's main data was effectively collected via Design Development Research (DDR) methodology instruments. The main study's goal is to develop an Assistive Mobility Design System (AMDS) for groups of persons with disabilities (PWDs), As knowledge contribution, this study will assist to develop a novel system for those with disabilities (PWDs) to enhance their quality of life for end users. It provides guidance for industrial designers, manufacturing engineers, and specific community to understand about Disable Product Design and users need and requirements.